Qu’est-ce qu’une hérésie littéraire ? Robert de Boron et les Hauts Livres du Graal - Jean-René Valette (Revue des Langues Romanes)
Among the novels of the Grail, the works attributed to Robert de Boron (early thirteenth century) are those whose link with heresy has been most often reported (with the Catharisms as well as with the thought of Joachim de Flore and those who constitute his true posterity, the “spiritual” Franciscans). The manifestation of heresy in these texts is so significant and at the same time so delicate to circumscribe that there has been talk of “a kind of literary heresy, of what could be called the heresy of the Grail, or even of literature as heresy” (F. Zambon). On this double level (heresy in novel writing, heresy as writing), we intend to revisit this subject in the light of the progress made in research, focusing both on works that reassess the heretical phenomenon and on those that invite reflection on the complex status of the literary text in the Middle Ages.